Peningkatan Kemampuan Menulis Surat Lamaran Pekerjaan Melalui Model Pembelajaran Think-Pair-Share - Turmi Ngestiningsih (EduInovasi: Journal of Basic Educational Studies, 2022)
The purpose of the study was to find out how the ability to write job application letters for class XII students of SMK Negeri 2 Depok City in 2019-2020 and to find out whether cooperative learning with the Think-Pair-Share model could improve the ability to write cover letters for class XII students of SMK Negeri 2 Depok City. This study uses classroom action research (action research) in two rounds (cycles). Each round consists of four stages, namely: planning, activities and observations, reflection, and revision. The target of this research is Class XII Computer Network Engineering (TKJ) SMK Negeri 2 Depok City in 2019-2020. The data obtained in the form of subjective test results and observation sheets of teaching and learning activities. The results show, class XII students of TKJ SMK Negeri 2 Depok City in 2019-2020 are able to write job applications. This can be seen from the average score of students' ability to write job application letters and student learning completeness in cycle I and cycle II has increased. The average score of students' ability to write job application letters in the first cycle was 72.77 and learning completeness reached 64.70%. The average score of students' ability to write job application letters in cycle II was 78.38 and learning completeness reached 85.29%. The application of the Think-Pair-Share model of cooperative learning has a positive influence on Teaching and Learning Activities (KBM). Think-Pair-Share model of cooperative learning can improve student learning outcomes. This is indicated by the average student answers stating that students are interested and interested in the Think-Pair-Share cooperative learning method so that they become motivated to learn. Keywords: Writing Ability, Cooperative Learning, Think-Pair-Share Learning Model